The effect of transcranial alternating current stimulation on functional recovery in patients with stroke: a narrative review - Yang, Seoyon; Yi, You Gyoung; Chang, Min Cheol (Frontiers in Neurology, 2024)
Stroke is a common neurological disorder worldwide that can cause significant disabilities.Transcranial alternating current stimulation (tACS) is an emerging non-invasive neuromodulation technique that regulates brain oscillations and reshapes brain rhythms. This study aimed to investigate the effect of tACS on functional recovery in patients with stroke.The MEDLINE (PubMed), Cochrane Library, Embase, SCOPUS, and Web of Science databases were searched for English-language articles on tACS and stroke, published up to October 20, 2023. The following key search phrases were combined to identify potentially relevant articles: 'tACS,' 'transcranial alternating current stimulation,' 'stroke,' 'cerebral infarct,' and 'intracerebral hemorrhage.' The inclusion criteria for study selection were as follows: (1) studies involving patients with stroke and (2) studies that used tACS for functional recovery. A total of 34 potentially relevant studies were identified. Five articles were included in this review after reading the titles and abstracts and assessing their eligibility based on the fulltext articles. Among the included studies, one investigated the improvement in overall functional status in patients with stroke after tACS, and two investigated the effect of tACS on motor function and gait patterns. Moreover, one study reported the efficacy of tACS on aphasia recovery, and one study evaluated the effect of tACS on hemispatial neglect. Our findings suggest that tACS improves functional recovery in patients with stroke. The application of tACS was associated with improved overall functional recovery, sensorimotor impairment, aphasia, and hemispatial neglect. The potential clinical application of tACS should be supported by high-quality, evidence-based studies.